Transoral surgery for oropharyngeal tumors using the Medrobotics® Flex® System – a case report. (2015) - Mandapathil, Magis; Duvvuri, Umamaheswar; Güldner, Christian; Teymoortash, Afshin; Lawson, George; Werner, Jochen A
Highlights: Transoralvisualisation of pharyngeal tumors is feasible using the novel Medrobotics ® Flex ® System. Transoralresection of pharyngeal tumors with a monopolar cautery is feasible using the novel Medrobotics ® Flex ® System. The flexibility of the endoscope and instruments allow for good access and visualisation of target structures within the pharynx. Abstract: Introduction: Transoral resection of pharyngeal tumors with acceptable oncological and functional results can be challenging due to their location in a narrow anatomic space. Case presentation: In this case report, we demonstrate successful visualization and resection of a squamous cell carcinoma of the oropharynx using the novel Medrobotics ® Flex ® System. The Medrobotics ® Flex ® System (Medrobotics Corp., Raynham, MA, USA) is an operator controlled flexible endoscope system that includes a rigid endoscope and computer-assisted controllers, with two external channels for the use of compatible, 3.5 mm flexible instruments. Discussion: In a 74-year old female patient a T1 squamous cell carcinoma of the oropharynx was visualized and completely resected using this system. The Medrobotics ® Flex ® System is a promising device for transoral approaches in resection of tumors within the pharynx. Conclusion: Good visualization, access, and flexibility of the endoscope and instruments are hereby clear advantages of the system compared to commonly used systems.